Analisis Kandungan Padatan Tersuspensi Total Berdasarkan Karakteristik Hujan di Daerah Aliran Sungai Ciliwung - Sulistyo Ariebowo Djajusman; Hadi Susilo Arifin; Etty Riani (Graduate School Bogor Agricultural University (SPs IPB), 2020)
Total suspended solid (TSS) is one of the parameters that determines whether or not a body of water is polluted. One factor that influences the amount of TSS content is the characteristic of rainfall in an area. Purpose of this study was to determine the relationship between the effect of rainfall characteristics and TSS content in Ciliwung River. Multiple regression analysis was used for analytical method. Results of multiple regression analysis showed that the correlation coefficient (adjusted R2) for the factors of rainfall, discharge and sediment show a low correlation to changes the content of TSS in Ciliwung River. The value of each correlation coefficient in the upstream, middle, and downstream of Ciliwung River are 0.21, 0.31, and 0.09 respectively. According to the F test, rainfall, discharge and sediment were significantly affect TSS content in the upstream and middle stream. Based on t test, it is known that only rainfall affect TSS content in the upstream and midlle stream.